STRATEGI KEPALA SEKOLAH DALAM MEWUJUDKAN KELAS UNGGULAN DI SMA SAINS AL-QUR’AN WAHID HASYIM YOGYAKARTA - Trisandi Trisandi; Abd Adam Salam (MANAGERE : Indonesian Journal of Educational Management, 2020)
This article discusses the principal's strategy in realizing superior classes at Wahid Hasyim Yogyakarta's Al-Qur'an Science High School. The superior class is given the name international class which is one of the principals' strategies to improve school quality and public trust in the institution. The emergence of superior classes as an encouragement, especially for other classes to further optimize the development of students' interests and talents. This research uses descriptive qualitative method by collecting data by observation, interview and documentation. The results of this study indicate that the principal's strategy in realizing superior classes has a very large impact on the development of students' interests and talents, especially on excellent programs offered by international classes such as science, foreign languages and tahfidz. The program as an international class flagship program to be able to compete globally is proven by the achievements that have been achieved at the national and international levels